POTRET USAHA KECIL DAN MENENGAH DI KABUPATEN PONOROGO PASCA PEMBINAAN - Rapini, Titi; Farida, Umi; Adji, Setyo (Jurnal Ilmu Manajemen, 2016)
The purpose of this research to know the increase in the financial performance of Small and Medium Enterprises after establishment is done by the Department Indagkop Ponorogo. Knowing that it can also increase the efficiency and effectiveness of the guidance that has been done. Besides that, to know the barriers are faced by SMEs so that can be designed method / pattern of guidance suit the specific on the financial management.The scope of this research are in Ponorogo, where SMEs surveyed are SMEs that have followed the guidance by Indagkop during the period 2009 to 2013.The necessary data is data including data Primary barriers and obstacles is experienced by SMEs, financial data. It is obtained by direct interviews with a guide from the questionnaire. Secondary data include data of participants and types of training - coaching is done Indagkop PonorogoFrom the result of the research, it is known there are 3 types of training from 2009 to 2013. However, this data is not supported by its business, and the company name. Sample of 50 participants with a variety of year and type of training. The results are 52 % of participants have a business, 24 % have not, and 24 % did not find the address. While having a business, they do not have the financial data in writing. This indicates that SMEs do not yet have basic financial statements, which can be used to evaluate the performance of financial management